Effects of sitagliptin in diabetic patients with nonalcoholic steatohepatitis - (:unkn) unknown (UNIV CATHOLIQUE LOUVAIN-UCL, 2012)
Background & Aims : Preliminary evidence suggests that inhibition of dipeptidyl peptidase (DPP)-IV preserves pancreatic beta cell function in patients with type 2 diabetes (T2D). However, its effects on liver histology in nonalcoholic steatohepatitis (NASH), hepatic complication of diabetes, have not yet been adequately explored. The present open-label, single-arm observational pilot study investigated the effects of one year of treatment with a dipeptidyl peptidase-IV inhibitor, sitagliptin, on liver histology, body mass index (BMI), and laboratory parameters in NASH patients with T2D. Patients and Methods : Paired liver biopsies from 15 diabetic patients with NASH (7 males, 8 females; mean age : 49.7 +/- 8.1 years (range : 36-62)) before and after one year of therapy with sitagliptin 100 mg once daily were studied. Clinical and laboratory parameters were recorded. Results : Treatment with sitagliptin resulted in a significant decrease in ballooning (P = 0.014) and NASH scores (P = 0.04), while the reduction in the steatosis score was of borderline statistical significance (P = 0.054). These effects were accompanied by a significant reduction in body mass index, AST, and ALT levels. Conclusion : Our study suggests that sitagliptin ameliorates liver enzymes and hepatocyte ballooning in NASH patients with T2D and may have therapeutic implications. (Acta gastroenterol. belg., 2012. 75, 240-244).
Keywords: sitagliptin; diabetes; nonalcoholic steatohepatitis; dipeptidyl peptidase-IV inhibitor; DPPIV; DIPEPTIDYL-PEPTIDASE-IV; FATTY LIVER-DISEASE; GLYCEMIC CONTROL; DPP-IV; DISTURBANCES; VILDAGLIPTIN; INHIBITION; PREVENTS; THERAPY; DIET